Examining the cost of delivering routine immunization in Honduras. (7th May 2015) - Janusz, Cara Bess; Castañeda-Orjuela, Carlos; Molina Aguilera, Ida Berenice; Felix Garcia, Ana Gabriela; Mendoza, Lourdes; Díaz, Iris Yolanda; Resch, Stephen C.
Highlights: Routine immunization delivery costs US$ 32.5 million in Honduras for the year 2011. Non-vaccine system costs per dose applied ranged from US$ 25.55 to US$ 2.84. Non-vaccine system costs represent a significant proportion of total program costs. Cost per fully immunized child at age one amounts to US$ 132. Abstract: Background: Many countries have introduced new vaccines and expanded their immunization programs to protect additional risk groups, thus raising the cost of routine immunization delivery. Honduras recently adopted two new vaccines, and the country continues to broaden the reach of its program to adolescents and adults. In this article, we estimate and examine the economic cost of the Honduran routine immunization program for the year 2011. Methods: The data were gathered from a probability sample of 71 health facilities delivering routine immunization, as well as 8 regional and 1 central office of the national immunization program. Data were collected on vaccinations delivered, staff time dedicated to the program, cold chain equipment and upkeep, vehicle use, infrastructure, and other recurrent and capital costs at each health facility and administrative office. Annualized economic costs were estimated from a modified societal perspective and reported in 2011 US dollars. Results: With the addition of rotavirus and pneumococcal conjugate vaccines, the total cost for routine immunization delivery in Honduras for 2011 was US$ 32.5 million. Vaccines and related supplies accounted for 23% of the costs. Labor, cold chain, and vehicles represented 54%, 4%, and 1%, respectively. At the facility level, the non-vaccine system costs per dose ranged widely, from US$ 25.55 in facilities delivering fewer than 500 doses per year to US$ 2.84 in facilities with volume exceeding 10, 000 doses per year. Cost per dose was higher in rural facilities despite somewhat lower wage rates for health workers in these settings; this appears to be driven by lower demand for services per health worker in sparsely populated areas, rather than increased cost of outreach. Conclusions: These more-precise estimates of the operational costs to deliver routine immunizations provide program managers with important information for mobilizing resources to help sustain the program and for improving annual planning and budgeting as well as longer-term resource allocation decisions.